S14.1 The effect of anti-ribosomal-p and anti-dweys antibodies on depression and behavioral cognitive processes in systemic lupus erythematosus : an integrated clinical and functional MRI study. (27th September 2022) - Chessa, E; Porcu, M; Pintus, E; Perra, A; Floris, A; Angioni, MM; Congia, M; Carta, MG; Saba, L; Mathieu, A; Cauli, A; Piga, M
Abstract : Purpose: Cognitive dysfunction (CD) and mood disorders (MD) are among the most frequent neuropsychiatric (NP) events in Systemic Lupus Erythematosus (SLE), but their pathogenesis has not been fully clarified yet. A potential role of antineuronal antibodies in NP-SLE patients is currently being investigated. The primary aim of the study was to explore the effects of anti-ribosomal-P (anti-Rib-P) and anti-DWEYS antibodies on CDs and MDs and their relationship with functional Magnetic Resonance Imaging (MRI) brain connectivity in patients affected by SLE. Methods: A cross-sectional study was conducted between April 2019 and February 2020, including consecutive adult patients who fulfilled the ACR/EULAR 2019 SLE criteria. Demographics, serological, ongoing medications, SLEDAI and SLICC/Damage Index (SDI) were recorded. Serum level quantification for anti-Rib-P and anti-DWEYS antibodies were performed using an ELISA. A battery of neuropsychological testing exploring cognitive domains, depression and quality of life was interpreted by a neuropsychologist. A resting-state functional connectivity (rs-fc) MRI analysis was performed within 2 weeks since the neuropsychological status assessments. Two region of interest to region of interest (ROI-to-ROI) analyses with the graph theory was performed. Results: Thirty-three SLE patients (9% male) were enrolled, mean age 43.5 (+-14) years, and median disease duration of 10.4 years (IQR 2.9–25.4). The daily median prednisone (PDN) dose was 6.4 mg (3.8–13.5). Anti-Rib-P were positive (range 0–255 U/ml) in 6 patients (18.2%) and anti-DWEYS (range 0–1.8 OD) in 14 (42.4%). Nineteen out of 33 patients (57.6%) showed at least a cognitive test alteration. The most frequent cognitive deficits were memory disturbances, found in 6.1–27.3% of the population evaluated, according to the cognitive test used, followed by alterations in executive functions (12.1–21.9%), psychomotor speed (18.2%) and attention (3–12.1%), but no significant association with antibodies was found. Depression was found in 14 (42.4%) patients using the Center for Epidemiologic Studies Depression Scale (CES-D) as a screening instrument. In multiple regression backward models, after correction for age, disease duration, SLEDAI and SDI, the CES-D showed an independent association with anti-Rib-P titer (β=0.32 per U/ml; p=0.049) and PDN daily dose (β=0.38 per mg/day; p=0.023). The rs-fc MRI analysis revealed a statistically significant association between the titer of anti-Rib-P and many altered properties of the brain ROIs ( Figure 1 ), but no effects of PDN daily dose on specific cerebral networks. Conclusions: Anti-Rib-P antibodies and PDN daily dose are associated with depressive symptoms. Anti-Rib-P antibodies are also associated with changes in brain network properties in SLE patients, which add knowledge to their pathogenetic effect.